2010
DOI: 10.1016/j.jtcvs.2009.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year experience with off-pump coronary artery bypass grafting: Lessons learned from early postoperative angiography

Abstract: Early patency of venous grafts was significantly lower than that of arterial grafts. Intraoperative flowmetry and revision of abnormal grafts improved early graft patency, and reoperation according to early angiographic findings may further improve graft patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In general, the initial experience of performing OPCABG operations (performed generally in low-risk patients), based on numerous studies, could not convincingly demonstrate the advantages over performing such procedures on-pump. (5)(6)(7)(8) During the same period, the first reports on the results of OPCABG in high-risk patients appeared. (9) The milestone work was published by J.Puskas et al, (10) which convincingly demonstrated the advantages of OPCABG over on-pump CABG in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the initial experience of performing OPCABG operations (performed generally in low-risk patients), based on numerous studies, could not convincingly demonstrate the advantages over performing such procedures on-pump. (5)(6)(7)(8) During the same period, the first reports on the results of OPCABG in high-risk patients appeared. (9) The milestone work was published by J.Puskas et al, (10) which convincingly demonstrated the advantages of OPCABG over on-pump CABG in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…This proportion varies from 49% to 99%, according to the reports from different authors. (3)(4)(5)(6)(7)10,11) Leading groups in this area, such as J.Puskas' group, perform OPCABG operations in 99% of all cases. In our series of 300 isolated CABG operations, 270(90%) were performed off-pump.…”
Section: Discussionmentioning
confidence: 99%
“…These results meant a 96% overall graft patency. In their recent study Kim et al [5] performed early postoperative angiography to assess anastomosis accuracy and patency after off-pump coronary artery bypass grafting in 1345 patients between 1998 and 2007. Of the 1345 patients, 1278 patients (95.0%) underwent early postoperative angiography on postoperative 1.6±1.2 days.…”
Section: Patency Rates After Cabgmentioning
confidence: 99%
“…Despite its highly favorable outcomes, a significant number of patients suffer early graft failure after CABG. Several angiographic studies have demonstrated that up to 15% of saphenous vein grafts and 8% of left internal thoracic artery grafts are occluded in the very early postoperative period of CABG [1][2][3][4][5][6]. If identified, this problem may be repaired shortly after or at the time of the operation because it is thought to be mainly a result of a surgical or technical problem.…”
Section: Introductionmentioning
confidence: 99%
“…The basic surgical procedures and strategies of OPCAB have been previously described (6,7). During the study period, we changed revascularization strategies based on our patency study after OPCAB (6); however, the left internal thoracic artery has continuously been used as the first conduit of choice for CABG.…”
Section: Operative Techniquementioning
confidence: 99%